Direct Synthesis of Deuterium-Labeled O-, S-, N-Vinyl Derivatives from Calcium Carbide - Ledovskaya, Maria S.; Voronin, Vladimir V.; Rodygin, Konstantin S.; Posvyatenko, Alexandra V.; Egorova, Ksenia S.; Ananikov, Valentine P. (Synthesis, 2019)
A novel methodology for the preparation of trideuterovinyl derivatives of high purity directly from alcohols, thiols, and NH-compounds was developed. Commercially available calcium carbide and D2O acted as a D2-acetylene source, and DMSO-d6 was used to complete the formation of the D2C=C(D)–X fragment (X = O, S, N). Polymerization of a selected trideuterovinylated compound showed a very promising potential of these substances in the synthesis of labeled polymeric materials. Biological activity of the synthesized trideuterovinyl derivatives was evaluated and the results indicated a significant increase of cytotoxicity upon deuteration.
Keywords: deuterium labeling; deuteration; deuterated drugs; vinylation; calcium carbide